Ethical leadership status and performance health of Education workers - Fahimeh Forootani; Alireza Manzari Tavakoli; Sanjar Salajegheh; Mahdi Mohammad Bagheri (Shahid Beheshti University of Medical Sciences, 2024)
Background: Ethical managers provide mutual trust in the organization by increasing the authority to act, which increases interest in work. This study was conducted with the aim of investigating the Ethical leadership status and performance health of Education workers. Methods: This study was applied, descriptive and by survey method on 341 Education workers in Kerman province, in which the samples were selected by stratified random method and included in the study. Data collection was done on 46 questions and job performance questionnaire including 28 questions. 30 specialists used the Delphi technique to assess the components' dependability, and AMOS software was installed. A Cronbach's alpha coefficient greater than 0.7 revealed the items' internal consistency and verified their dependability. Software called SPSS-22 was utilized to analyze the data. Results: The results show that the status of ethical leadership and its components are favorable among employees, and the status of job performance and its task dimension are not favorable, and this variable was favorable only in the contextual dimension. The components of job enthusiasm (behavioral, cognitive and emotional) which are considered as predictors of job performance, have a significant difference in which there is a relationship between job enthusiasm and ethical leadership of healthcare workers. Conclusion: The results of job enthusiasm with the mediation of moral leadership show the strengthening of employees' performance health. By identifying the influencing factors related to job performance and work enthusiasm, managers can help to better understand the nature of employees' performance and work enthusiasm.